Debarment and collusion in procurement auctions - Claudia Cerrone; Yoan Hermstrüwer; Pedro Robalo (Max Planck Institute for Research on Collective Goods, 2018)
This paper explores the impact of debarment as a deterrent of collusion in first-price procurement auctions. We develop a procurement auction model where bidders can form bidding rings, and derive the bidding and collusive behavior under no sanction, debarment and fines. The model's predictions are tested through a lab experiment. We find that debarment and fines both reduce collusion and bids. The deterrent effect of debarment increases in its length. However, the debarment of colluding bidders reduces effciency and increases the bids of non-debarred bidders. The latter suggests that the market size reduction resulting from debarment may trigger tacit collusion.
Keywords: C92; D03; D44; K21; K42; 330; debarment; collusion; procurement auctions; procurement law; sanctions